Predictors of Severe Acute Malnutrition among Children Aged 6 to 59 Months Attended out Patient Therapeutic Program Center in Kavre District of Nepal - A Case Control Study - Bhandari, Rajan; Khatri, Sangita Kumari; Shrestha, Khadga Bahadur (International Journal of Child Health and Nutrition, 2018)
Background: Severe acute malnutrition is an excessive loss of weight due to the acute shortage of food or illness. It is one of the major public health problems in developing countries including Nepal. According to multiple indicator cluster survey (MICS) 2014, 2.6% severely malnourished in Nepal and 4.4% are severely malnourished in Kavre district. However, there are limited studies about predictors of severe acute malnutrition in Nepal. Thus, this study was aimed to identify the predictors of severe acute malnutrition in Kavre district of Nepal. Methods: Health facility based matched case control study was conducted among 210 (70 cases and 140 controls) children aged 6-59 months from November 2015 to April 2016. Data was collected through face to face interview with mother of eligible children using structured questionnaires. Multivariate analysis was applied to estimate adjusted odds ratio along with 95% confidence interval. Results: Children with severe acute malnutrition were 11.32 times more likely than control to have recurrent diarrhea in past six months (95% CI=4.64-28.21). Similarly, severe acute malnutrition was associated with female sex (AOR=2.44, 95% CI=1.88-6.78), fathers occupation daily labor (AOR=4.69, 95% CI=1.17-13.76) and agriculture (AOR=6.850, 95%CI=3.81-12.93), improper exclusive breast feeding (AOR=6.646, 95%CI=2.11-20.90), not feeding colostrum (AOR=3.89, 95% CI=2.88-11.21), severe food insecurity access (AOR=3.55, 95% CI=1.85-9.77) and monthly income less than average level (AOR=8.214, 95% CI=1.43-22.16). Conclusion: Severe acute malnutrition was independently associated with sex of child, occupation of father, monthly household income, not feeding colostrum, improper exclusive breast feeding, severe household food insecurity access and recurrent diarrhea.